CHALLENGES OF FISH PRODUCTION AND FISHERFOLKS AT SOME FISHING COMMUNITIES IN SOUTHERN IJAW LOCAL GOVERNMENT AREA OF BAYELSA STATE - AGBABIAKA, L. A.; NNADI, E.A.; OKOGBUE, B. C. (Nigerian Journal of Fisheries, 2025)
This study was conducted to evaluate the fish production pattern and the livelihoods of the fisherfolks at the Southern Ijaw Local Government Area (SILGA) of Bayelsa State. Data collection was done using snowballing approach in stratified random sampling with structured questionnaire programmed in an electronic application “KoboCollect” and semi- structured interviews (SSI) for target groups in thirteen (13) selected fishing communities. The main occupation of respondents in sampled area revealed capture fisheries (fishing) dominance with a percentage of 90.91% compared to aquaculture which contributed only 9.09% of the total fish production in the Local Government Area (LGA). It was also observed that the fisherfolks do not have access to basic amenities such as potable water, good housing, toilet facilities, electricity and access to quality education. Rudimentary fishing expeditions majorly observed are in wooden canoes and paddles with very few motorized boats. Challenges of fish production due to insecurity in the area includes poor access to credit facilities from banks, incessant flooding due to climate change, lack of cold chain facility, inaccessibility to National grid; better farming practices and inputs including lack of aquatic veterinarians to combat fish diseases in the study area. There is urgent need for sustainable livelihood programmes, improved infrastructural facilities and technological supports to boost production via aquaculture value-chain and enhance income that will improve their standard of living.